MEDIATING ROLE OF TRUST IN TAM AND DIRECT UTAUT EFFECTS ON DIGITAL PAYMENT INTENTION - Budiman, Johny; Verni; Kesumahati, Erilia (Universitas Islam Negeri Alauddin Makassar, 2025)
This study examines the factors influencing consumers' readiness to embrace digital payment systems, with the objective of enhancing a customer-centric approach to the implementation of financial technology. Structured questionnaires were used in a quantitative approach with a total 314 data collected, and SPSS was used for descriptive analysis, and SmartPLS to look at the structural relationships between the constructs. Perceived ease of use, perceived usefulness, performance expectancy, social influence, and trust (as a mediating factor) are the main variables. The results show that perceived usefulness (p = 0.027), trust (p = 0.000), performance expectancy (p = 0.000), and social influence (p = 0.000) are all positively correlated with the intention on digital payments. Trust demonstrated a significant mediating role in strengthening these relationships. However, perceived ease of use (p = 0.586) did not show a significant impact on intention. These results highlight the importance of trust in digital payment adoption and suggest that future studies may focus on MSMEs’ readiness for financial technology integration. Keywords: Perceived Ease of Use, Perceived Usefulness, Trust, Performance Expectancy, Social Influence, Intention on Digital Payment